ANALYSIS OF FACULTY SCIENTIFIC WORKS CITATIONS IN STUDENTS' THESES ON GOOGLE SCHOLAR WEBSITE IN THE LIBRARY SCIENCE STUDY PROGRAM FOR THE PERIOD 2019–2024 - Sugiri, Tiara Dwi Handayani; Fathurrahman, Muslih (International Journal of Cultural and Social Science, 2025)
This study maps the use of faculty publications in undergraduate theses at the Department of Library Science, UINSU, during 2019–2024. A sample of 50 undergraduate theses from the institutional Publish or Perish was analyzed at the reference-entry level, while faculty works were identified via Google Scholar/SINTA. Descriptive statistics and bibliometric visualizations (network, overlay, and density) were produced using VOSviewer. The results show that, out of 1,634 references, only 8 citations to faculty works were found across 6 undergraduate theses (approximately 0.48%). The maps indicate fragmented connections, a strong reliance on external sources, and the absence of a cohesive citation cluster centered on internal faculty publications. These findings suggest low visibility and uptake of faculty works in student writing. Implications include a relevance-based minimum citation policy (e.g., at least 1–2 appropriate faculty citations per thesis), curated topical reading lists of faculty publications, ongoing information-literacy and reference-management training, and improved digital visibility through optimized Google Scholar/SINTA profiles and institutional repository presence.